2019
DOI: 10.1002/acm2.12675
|View full text |Cite
|
Sign up to set email alerts
|

Peer support: A needs assessment for social support from trained peers in response to stress among medical physicists

Abstract: Purpose Previous studies suggest that within radiation oncology, medical physicists (MP) experience high workloads. Little is known about how MPs use social support (SS) in times of stress. Methods In collaboration with the Workgroup on Prevention of Medical Error, the American Association of Physicists in Medicine administered this Human Investigation Committee (HIC) approved email survey to 8566 members. Respondents were considered likely to seek SS if they answered (probably/definitely would) and unlikely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Understanding the challenges faced by medical physicists is essential given the substantial levels of burnout among this population. In a recent study of medical physicists, 33% of respondents reported experiencing burnout, 8 which is similar to the 42% burnout rate among oncology physicians. 9 Mazur et al found that medical physicists reported quantitatively high workloads and mental demand levels in comparison with other radiation oncology professionals.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Understanding the challenges faced by medical physicists is essential given the substantial levels of burnout among this population. In a recent study of medical physicists, 33% of respondents reported experiencing burnout, 8 which is similar to the 42% burnout rate among oncology physicians. 9 Mazur et al found that medical physicists reported quantitatively high workloads and mental demand levels in comparison with other radiation oncology professionals.…”
Section: Introductionmentioning
confidence: 71%
“…10 Medical physicists also express an uncertainty in how or even if to seek out and receive wellness-related support. 8 Left unaddressed, burnout in this group of health care professionals may lead to similar consequences as for physicians, including a potential effect on the quality of patient care. 9,11,12 Little published information exists to inform interventions to reduce burnout for physicists or whether existing interventions translated from other areas of health care may be successful.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary data from my own institution suggests that physics chart reviews are completed faster while working from home. Given the concerning data that >40% of medical physicists experience burnout, increasing work‐life balance through flexible work options is a novel solution, which also could improve patient safety with less burnout of healthcare workers 12 . Through these days of the COVID‐19 pandemic, we will gain necessary experience to evaluate productivity and effectiveness of telecommuting medical physicists.…”
Section: For the Proposition: Holly Lincoln Msmentioning
confidence: 99%
“…Health care professionals in general report several coping mechanisms to alleviate such symptoms. An important coping mechanism includes social support from colleagues, family, hospital management and friends, albeit that such interactions are felt to be meaningful to some extent (Johnson et al., 2019; Kable et al., 2018; Baas et al., 2018; Seys et al., 2013a; Seys, Wu, et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although some peer support systems are described in recent literature, it remains unclear (Scott, 2010; Seys, Scott, et al., 2013) what type of support is best offered to health care providers in the aftermath of a PSI and who can provide such support (Johnson et al., 2019). The aim of this study therefore was to investigate health care professional's (nurses and doctors) preferences pertaining to support in the aftermath of a PSI and potential variation depending on the level of patient harm.…”
Section: Introductionmentioning
confidence: 99%